Pengaruh Model Pembelajaran dan Kecerdasan Emosional terhadap Hasil Belajar Peserta Didik - Ramadhan, Puji Laila; Anwar, Muhammad; Sudding, Sudding (Chemistry Education Review (CER), 2020)
This study aims to determine the effect of the influence of learning models and emotional intelligence on learning outcomes of XI grade students of SMA Negeri 12 Makassar. This research method uses quasi-experimental methods used is "factorial design 3 x 3". Data analysis using the normality test, homogeneity test, hpotesis test and for hypothesis testing is done by one way ANOVA at a significant level of 0.05. The results of the analysis show the average value of student learning outcomes in experimental class 1 in the posttest is 51.89, experimental class 2 is 60.50 and experimental class 3 is 63.47. The average percentage of emotional intelligence in the low category is 59.6, in the moderate category is 36.11 and the value of the category 55.14 is in the high category. The results of testing the hypothesis 1 used analysis of variance (ANOVA) with the SPSS version 22 for windows program at a significant level, α = 0.05, obtained a significance value (0.313 > 0.05), indicating the hypothesis was rejected. It was concluded that there was no influence of learning models and emotional intelligence on student learning outcomes. Hypothesis 2 test results at a significant level, α = 0.05 obtained significance value (0.997 > 0.05), indicating the hypothesis was rejected. It was concluded that there was no influence of emotional intelligence on student learning outcomes. The results of testing the hypothesis 3 at a significant level, α = 0.05 obtained a significance value (0.583 > 0.05), indicating the hypothesis was rejected. It was concluded that there was no interaction between learning models and emotional intelligence on learning outcomes of classroom students.